Local Wisdom on Lexicon in Rice Field Agriculture - Novita Puspahaty; Dian Indira; Wahya; Susi Machdalena (Universitas Muhammadiyah Surakarta, 2026)
Globalization had a great impact to language use not only to national language, like Indonesian, butalso to local languages and cultures. This research examines the lexicon of rice field agriculture in BekasiRegency and its local wisdom based on anthropolinguistics study. We employ ethnographic researchmethodology to gain insight into the research aim. We select nine informants who were representativesof the residents of Sukakarya, Sukatani, Serang Baru, and Cibarusah districts. The informants wereactive in rice field agriculture and actively use their mother tongue so that they were considered able toprovide the information needed. The result of the research shows that: (1) the total of 99 lexicon relatedto rice field agriculture were found in Bekasi Regency. The lexicons show the language system embracedby the people of Bekasi Regency, the technological system, the economic system, the knowledge system,and the religious system. (2) local wisdom that appears in Bekasi Regency are 15 types of 17 types oflocal wisdom mentioned by Sibarani. We urge the people of Bekasi Regency to harmonize the impact ofglobalization and their local wisdom, to safeguard Bekasi’s indigenous language and culture.